Economics of education and prospects for its development - Sabodash, Olga Aleksandrovna; Kalyakina, Inessa Makedonovna; Kosnikov, Sergey Nikolaevich; Elizarova, Nadezda Sergeevna; Borisov, Egor Aleksandrovich; Sorgutov, Ilya Valerievich (Linguistics and Culture Review, 2021)
The article considers the prospects for the development of the education economy in modern market conditions. The main reason for considering this topic is that in the modern period, this science is immature, since it does not demonstrate the ability to offer effective, efficient, socially feasible and economically viable solutions to educational problems. Accordingly, the main direction of the development of this science should be considered the development of scientific fundamental and technological approaches to solving existing problems in education. One of the tools in this regard should be called educational projects that contribute to the dynamic development of both pedagogy in general and this science in particular. To be recognized as an integrated field of research, the economics of education should assign to pedagogy the role of helping scientists to create formative solutions to the criticisms identified in the course of economic research. Indeed, within the framework of the role that pedagogy can assume, planning in the field of education, the formation of various aspects of personality (economic, financial, social and human) can be developed.